World Models as Organizational Models: Global Framing and Transnational Activism in the Brazilian Black Movement - Rosa, Alexandre Reis (Organizações & Sociedade, 2018)
The aim of this article is to explore the appropriation that the Brazilian black movement makes of diasporic content. Throughout history the black diaspora has produced different meanings of what it is to be black, of what racism is, and produced different ways to fight it. Among these visions is the Black Atlantic, which presents itself as a macrostructure capable of influencing the formation of several frames around the world. The frames are interpretative schemes, world views that serve as a guide for the action of social movements, forming microstructures that represent the diagnoses and prognoses developed during their activities and proposals for struggle, as well as in its organization, forms of action, and resource mobilization. The results show that all these dynamics are related to the alignment of black activism to what is called global framing, which is a process of transnational diffusion formed during local adaptation processes.